Exploring the Association of Leukocyte Telomere Length and Hearing Threshold Shifts of Adults in the United States - Long, Lili; Meng, Zhaoli; Jia, Zhenchao; Tang, Xinghua (Frontiers in Aging Neuroscience, 2022)
Background: Although telomere length has a significant relationship with various age-related diseases, studies on its relationship with hearing status in adults are limited and equivocal. This study investigated the associations between mean telomere length (MTL) and low-, speech-, and high-frequency hearing threshold shifts of adults in the United States. Methods: A total of 2027 adults aged 20-69 years from the National Health and Nutrition Examination Surveys (NHANES, 1999–2002) were included in the analytic sample. The quantitative polymerase chain reaction method was used for the MTL assay, and MTL was expressed using the telomere-to-single copy gene (T/S) ratio. Hearing loss was defined as a pure tone average (PTA) for the better ear ≥ 20 dB HL at frequencies 500, 1000, 2000 and 4000 Hz. Univariate and multivariate linear regression analyses and smooth curve fittings were conducted to evaluate the correlation between MTL and low-, speech-, and high-frequency hearing levels. Results: The mean age of the participants was 40.60 ± 12.76 years, including 952 men (weighted, 48.67%) and 303 (weighted, 12.88%) participants with hearing loss. After adjusting for potential confounders in the multivariate linear regression model, the relationship between MTL and hearing thresholds was not statistically significant. Smooth curve fittings indicated a nonlinear relationship between MTL and high-frequency PTA hearing threshold shifts. MTL was inversely related to high-frequency PTA to the turning point (T/S ratio = 0.82) (adjusted β -21.45, 95% CI -37.28, -5.62; P = 0.008). When the T/S ratio exceeded 0.82, MTL was not associated with high-frequency PTA (adjusted β 0.18, 95% CI -2.21, 2.57; P = 0.8809). Conclusions: Our findings revealed That MTL was associated with high-frequency PTA hearing threshold shifts of adults in the United States in a non-linear manner.